2019
DOI: 10.1016/j.physbeh.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Background odors affect behavior in a dot-probe task with emotionally expressive faces

Abstract: Background odors affect behavior in a dot-probe task with emotionally expressive faces Odors affect perception of social cues in visual environments. Although often underestimated, people use their sense of smell to guide approach or avoidance behavior in social contexts. However, underlying psychological mechanisms are not well known. Prior work suggested olfactory effects are due to increased attention or arousal, or depend on the congruency between olfactory and visual cues. Our aim was to assess how odors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…The right-hemisphere effect is consistent with results from our team that the face-sensitive N170 ERP component is more prominent in the right hemisphere; furthermore, our study showed that the responsivity of the N170 to disgusted faces is enhanced by an unpleasant odor (Syrj€ anen et al, 2018). Another recent study investigated whether odors might direct attention toward odor-congruent happy and disgusted facial expressions in a dot-probe task (Syrj€ anen et al, 2019). However, this study's results gave no evidence that attention was automatically directed toward odor-congruent facial expressions.…”
Section: Odor Effects On the Processing Of Face Stimulisupporting
confidence: 92%
“…The right-hemisphere effect is consistent with results from our team that the face-sensitive N170 ERP component is more prominent in the right hemisphere; furthermore, our study showed that the responsivity of the N170 to disgusted faces is enhanced by an unpleasant odor (Syrj€ anen et al, 2018). Another recent study investigated whether odors might direct attention toward odor-congruent happy and disgusted facial expressions in a dot-probe task (Syrj€ anen et al, 2019). However, this study's results gave no evidence that attention was automatically directed toward odor-congruent facial expressions.…”
Section: Odor Effects On the Processing Of Face Stimulisupporting
confidence: 92%
“…The right-hemisphere effect is consistent with results from our team that the face-sensitive N170 ERP component is more prominent in the right hemisphere; furthermore, our study showed that the responsivity of the N170 to disgusted faces is enhanced by an unpleasant odor (Syrjänen et al, 2018). Another recent study investigated whether odors might direct attention toward odor-congruent happy and disgusted facial expressions in a dot-probe task (Syrjänen, Fischer, & Olofsson, 2019).…”
Section: Odor Effects On the Processing Of Face Stimulisupporting
confidence: 91%
“…However, one study did not find any effect of pleasant odors on classifying neutral faces as either pleasant or unpleasant, which might indicate that binary classifications of faces are less sensitive than ratings to the presumably subtle influence of odors (Bensafi, Pierson, et al, 2002). Several studies have shown that faces, regardless of expression, are rated as more arousing and that the face valence is affected in the direction of the odor valence (Syrjänen et al, 2019;Syrjänen et al, 2018). However, results are not entirely consistent in this literature.…”
Section: Odor Effects On Evaluations Of Facesmentioning
confidence: 69%
“…First, the odors were presented constantly over the duration of an experimental block. This might have resulted in habituation (Smeets and Dijksterhuis, 2014) to the smell, and suppression of its effect, although similar studies in our lab has shown no evidence of habituation (Syrjänen et al, 2017(Syrjänen et al, , 2019. To confirm the null effect of odors (or to find evidence for its existence), further research is needed where odor cues are brief and paired with each target stimulus (as they are in a priming task) rather than serving as background odors.…”
Section: Discussionmentioning
confidence: 76%
“…Based on our previous psychophysical investigations, a 30% concentration corresponds to a moderate intensity for both odors (Syrjänen et al, 2017). Participants were exposed to odors via cotton pads placed in tube-shaped cotton bands, tied under their noses -a method that has proved efficient in previous studies (Syrjänen et al, 2017(Syrjänen et al, , 2019. All three odor-conditions were manipulated within participants.…”
Section: Odor-conditionsmentioning
confidence: 99%